On-surface synthesis and characterization of tetraazanonacene - Ruan, Zilin; Ye, Liping; Singh, Yogendra; Naumann, Tim; Kang, Faming; Liu, Ye; Mastalerz, Michael; Gottfried, J. Michael (Angewandte Chemie. International edition, 2025)
Isosteric replacement of CH units of acenes by nitrogen induces significant changes in their electronic, redox, and spectroscopic properties. Here, we describe the on-surface synthesis of a nonacene analogue substituted with four nitrogen atoms on a Au(111) surface by a two-step atom manipulation, employing a bis vinylene-bridged precursor synthesized in solution. The generated tetraazanonacene has been investigated by scanning tunnelling microscopy/spectroscopy (STM/STS) and noncontact atomic force microscopy (nc-AFM), combined with first-principles calculations. We found that, compared to the pristine nonacene, the electronegative nitrogen atoms lower the frontier orbitals, resulting in an increased STS transport gap of 1.49 eV. Furthermore, the formation of four pyridine-like rings induces a stronger modulation of the aromaticity in tetraazanonacene compared to substitution patterns where nitrogen atoms form pyrazine-like rings. This observation is different from the nucleus independent chemical shift investigation of previous reported tetraazaundecacene, for which a stronger open-shell character is expected. Our work provides access to the synthesis of extended azaacenes and to an understanding of their properties.